1990
DOI: 10.1055/s-2007-1004852
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Forskolin-Induced Increase of cAMP by Diamide and N-Ethylmaleimide in Rat Pancreatic Islets

Abstract: In isolated rat pancreatic islets, the effect of diamide and N-ethylmaleimide (NEM) on forskolin- as well as on glucagon-induced elevation of cAMP was studied. Forskolin and glucagon increased cAMP levels in batch-incubated islets. Diamide and NEM further augmented forskolin-induced increase of cAMP levels, whereas glucagon-stimulated elevation of cAMP was not affected. From our data it is likely that under the conditions of the present study, the thiols related to the Ns-protein and the catalytic unit are ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In thyroid cells and pancreatic islets, diamide has been demonstrated to either potentiate or inhibit cAMP accumulation depending on the concentration used (35, 36). Therefore, we measured increases in cAMP and ATP release in response to direct activation of Gi with MAS7 and receptor-mediated activation of Gs with the ILO in the absence and presence of diamide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In thyroid cells and pancreatic islets, diamide has been demonstrated to either potentiate or inhibit cAMP accumulation depending on the concentration used (35, 36). Therefore, we measured increases in cAMP and ATP release in response to direct activation of Gi with MAS7 and receptor-mediated activation of Gs with the ILO in the absence and presence of diamide.…”
Section: Discussionmentioning
confidence: 99%
“…Since diamide is an oxidizing agent, we wished to establish that this agent did not directly inhibit either Gi-or Gs-associated signaling pathways for ATP release from erythrocytes or the ability of these cells to synthesize ATP. In thyroid cells and pancreatic islets, diamide has been demonstrated to either potentiate or inhibit cAMP accumulation depending on the concentration used 30,31 Therefore, we measured increases in cAMP and ATP release in response to direct activation of Gi with MAS7-and receptormediated activation of Gs with ILO in the absence and presence of diamide. We found that, similar to the effect of diamide on cAMP accumulation in other cell types, high concentrations (5 mmol/L) inhibited ILO-induced ATP release (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulatory glucose itself increases intracellular cAMP levels in islets in a dosedependent manner in parallel with its ability to enhance insulin secretion [12][13][14][15][16]. Forskolin [17] and isobutylmethylxanthine (IBMX), a phosphodiesterase inhibitor [16], also increase cAMP levels in islets [14,18] and enhance glucose-induced insulin secretion. cAMP and glucose together increase intracellular Ca# + Abbreviations used : FFA, non-esterified ('free') fatty acids ; F(1,6)P 2 , fructose 1,6-bisphosphate ; F(2,6)P 2 , fructose 2,6-bisphosphate ; GLP-1, glucagon-like peptide 1 ; HSL, hormone-sensitive lipase ; IBMX, isobutylmethylxanthine ; LC-CoA, long chain acyl-CoA ; PFK-1, phosphofructo-1-kinase ; PFK-2, phosphofructo-2-kinase ; PKA, protein kinase A ; RT, reverse transcriptase.…”
Section: Introductionmentioning
confidence: 99%